(untitled) (Alternate Horizons, 2021)
Peace and stability are among the most significant conditions capable of guaranteeing food security in all communities in the world. In fact, the constant availability and access to food is largely dependent on the state of peace. Armed conflicts in the world today have seriously affected food security with direct consequences on the economy, health, and standard of living of the affected population. This paper seeks to show how the ongoing armed conflicts in the North West and South West Regions of Cameroon between separatist armed groups and Cameroon defence forces have affected food security in many cities of Cameroon. It is argued in this paper that sustainable food security is strongly dependent on the degree of peace and security existing in a particular region. As such, effective conflict prevention and resolution can significantly contribute to guaranteeing food security to all communities in the world.